Implementation of Trajectory Tracking on Mobile Robot Differential Drive - Imam Taufiqurrahman; Sujarwanto, Eko; Andri Ulus Rahayu; Mira Riski Aldiani; Sayyid Qhutub Abdul Hakim (ULTIMA Computing, 2025)
Abstract—This study discusses the implementation of trajectory tracking on a differential drive mobile robot using the odometry method. The system was designed by utilizing rotary encoders to estimate the robot’s position and a proportional controller to regulate movement toward the target point. Experiments were carried out on multi-point trajectories, namely three-way and four-way paths, under two different surface conditions: flat and textured fields. The results showed that the robot was able to follow the predetermined path with a relatively high level of accuracy, especially on flat surfaces. However, on textured paths, the accuracy decreased due to wheel slip and disturbances in encoder readings. The comparison between both conditions emphasizes that surface characteristics have a significant influence on the performance of odometry-based trajectory tracking. Keyword — Mobile robot, differential drive, odometry, trajectory tracking, proportional control